Influence of seaweed Cystosiera crinitophylla as biostimulants on wheat seedling growth and development - Elbakkosh, Ali; Godeh, Masoud; Budabous, Fadila; Alkhfaify, AbdelKafe (Libyan Journal of Science &Technology, 2022)
The Objective of this study was to explore the effects of the Cystosiera crinitophylla extracts on the germination and seedling development of wheat (Triticum aestavium L.). We assessed seaweed cold and hot aqueous extract and ethanol extract (1:10 w/v) at different concentrations (2.5, 5, 10, and 20% v/v) on germination percentage and growth parameters of wheat seedlings under laboratory conditions. Additionally, the pot experiment was achieved to assess the effect of the biostimulant action of Cystosiera crinitophylla as a crude powder mixed with soil or foliar application on some growth parameters and photosynthetic pigments content of Triticum aestavium L. seedlings. The results demonstrated enhancement germination and growth at low extracts concentration, all the three seaweed extracts showed a better rate of germination and growth at optimum extracts concentration ranges between 5–10 % and toxicity at higher extracts concentration. In addition, the results of the pot experiment showed that the application of C. crinitophylla as a crude powder mixed with soil or cold aqueous extract, foliar spraying caused significant improvement in all the growth parameters and photosynthetic pigments of wheat seedlings. However, the enhancement was varied and could be application method and concentration-dependent. Furthermore, the preliminary phytochemical screening of seaweed showed the presence of phenolic compounds, flavonoids, tannins, alkaloids, carbohydrates, and proteins with high relative levels of some minerals. The results of the present investigation suggested that the application of biodegradable seaweed extracts is recommended to growers to manage improved germination, growth and of wheat.